Contact Lens Prescribing in Canada 2006 - Jones, Deborah A.; Woods, Craig A (Canadian Journal of Optometry, 2021)
A questionnaire was used to identify current preferences for contact lens prescribing in Canada. Practitioners were asked to submit information on the first ten patients fitted with contact lenses immediately after receipt of the survey; 151 completed questionnaires were returned, detailing contact lens fits to 1,421 patients. The results indicated that of the patients fitted with contact lenses, the majority were prescribed soft lenses. The preferred modality was monthly planned replacement. Over 80% of the soft lens fits were with either silicone hydrogel or mid-water content materials, with an even split between the two material options. Of the rigid lens fits the majority were for daily wear. The overnight wear of rigid lenses appears to be for the practice of orthokeratology. Practitioners are recommending multipurpose solutions for the majority of their soft lens patients (91%).